1979
DOI: 10.1161/01.hyp.1.1.31
|View full text |Cite
|
Sign up to set email alerts
|

The importance of vasopressin in the development and maintenance of DOC-salt hypertension in the rat.

Abstract: SUMMARY Experiments were performed to determine the role of vasopressin in deoxycorticosterone (DOC)-salt hypertension. In order to determine if vasopressin is necessary for the development of DOC-salt hypertension, rats with hereditary diabetes insipidus (DI) and normal Long-Evans rats (LE) were unilaterally nephrectomized, treated with DOC Pivalate (30 mg/kg • week) and given saline to drink for 8 weeks. A second group of DI rats were unilaterally nephrectomized, but received no treatment. Systolic blood pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
122
2

Year Published

1981
1981
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(130 citation statements)
references
References 18 publications
6
122
2
Order By: Relevance
“…20 - 22 Similar observations have been made in reduced renal mass hypertension. 19 In the present study, d(CH 2 ) 5 Tyr(Me)-AVP alone had no effect on blood pressure or heart rate in either hypertensive or normotensive rats.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…20 - 22 Similar observations have been made in reduced renal mass hypertension. 19 In the present study, d(CH 2 ) 5 Tyr(Me)-AVP alone had no effect on blood pressure or heart rate in either hypertensive or normotensive rats.…”
supporting
confidence: 69%
“…20 - 21 In addition, vasopressin-deficient Brattleboro rats are also protected against the development of DOC-saline hypertension. 22 " 24 Recent findings in our laboratory have indicated that one-kidney, figure-8 renal wrap hypertension is also a model of sodium-dependent hypertension. This form of hypertension is prevented when rats are maintained on a low sodium intake, while the hypertension is exacerbated when the rats are fed a high sodium diet.…”
mentioning
confidence: 99%
“…1 -2 By using some of these antagonists, several investigators were able to demonstrate a pressor role for AVP in normotension, 3 in maintaining blood pressure during hypovolemia, 4 -5 and in certain types of experimental hypertension. 6 Our own earlier studies with the compound d(CH 2 ) 5 -0-(Me)Tyr-AVP, revealed that the pressor function of AVP was most apparent on salt loading, 7 -8 was closely interrelated to those of the RAS and the SNS, and was maximized when the other two were impaired or eliminated. 910 These findings were confirmed and amplified subsequently by other investigators.…”
mentioning
confidence: 98%
“…2 A direct vasopressor role for AVP in the maintenance of hypertension in the DOCA-salt hypertension model is suggested by the finding of elevated plasma AVP levels and a fall in BP with intravenous administration of AVP antiserum 3 or VI receptor antagonist. 4 - 5 However, other investigators failed to demonstrate a reduction in BP with acute VI receptor blockade 68 or showed a reduction in BP with acute V2 or acute or chronic V1-V2 receptor antagonism 910 in DOCA-salt hypertension. Thus, the pressor roles of AVP and/or the VI and V2 AVP receptors in both the pathogenesis and maintenance of hypertension in DOCA-salt hypertension in the rat remain unclear.…”
mentioning
confidence: 99%